Anatomical and mechanical relationship between the proximal attachment of adductor longus and the distal rectus sheath1. Issue 4 (14th June 2012) - Norton‐old, Kimberley J.; Schache, Anthony G.; Barker, Priscilla J.; Clark, Ross A.; Harrison, Simon M.; Briggs, Christopher A.
Abstract: The objectives of this study were to investigate the anatomical relationship between the proximal adductor longus (AL) and rectus abdominis muscles and to determine whether unilateral loading of AL results in strain transmission across the anterior pubic symphysis to the contralateral distal rectus sheath. Bilateral dissections were conducted on 10 embalmed cadavers. Strain transfer across the pubic symphysis was examined on seven of these cadavers. An AL contraction was simulated by applying a controlled load in the direction of its proximal tendinous fibers, and the resultant strain in the contralateral distal rectus sheath was measured using a foil‐type surface mounted microstrain gage. Adductor longus attached to the antero‐inferior aspect of the pubis. In 18 of the 20 limbs, the proximal attachment of AL was tendinous on its superficial surface and muscular on its deep surface. The proximal AL tendon was found in most instances to have secondary communications with structures such as the contralateral distal rectus sheath, pubic symphysis anterior capsule, ilio‐inguinal ligament, and contralateral proximal AL tendon. Despite these consistent anatomical observations, strain measured in the contralateral distal rectus sheath upon unilateral loading of the proximal AL varied considerably between cadavers. Measured strain had an average ± 1SD of 0.23 ± 0.43%. The proximal attachment of AL contributes to an anatomical pathway across the anterior pubic symphysis that is likely required to withstand the transmission of large forces during multidirectional athletic activities. This anatomical relationship may be a relevant factor in explaining the apparent vulnerability of the AL and rectus abdominis attachments to injury. Clin. Anat. 2013. © 2012 Wiley Periodicals, Inc.